(untitled) (Swiss Medical Weekly, 2010)
Background: Interpersonal violence is a worldwide social reality which seems to increasingly affect even the safest of countries, such as Switzerland. In this country, road traffic accidents, as well as professional and recreational activities, are the main providers of trauma-related injuries. The incidence of penetrative trauma related to stab wounds seems to be regularly increasing in our ED. The question arises of whether our strategies in trauma management are adapted to deal efficiently with these injuries. Methods: To answer this question, the study analysed patients admitted for intentional penetrative injuries in a tertiary urban emergency department (ED) during a 23 month period. Demographics, conditions of the assault, injury type and treatments applied were analysed. Results: Eighty patients admitted due to an intentional penetrating trauma accounted for 0.2% of the surgical practice of our ED. The assault occurred equally in a public or a private context, mainly affecting young males during the night and the weekend. Sixty six patients (83%) were treated as out-patients. Only 10 patients needed surgery. None of them required damage control surgery. No patient died and the mean hospital stay was 5.5 days. Conclusions: The prevalence of stab wounds in Switzerland is low. These injuries rarely need complex, surgical procedures. Observational strategies should be considered according to the patient status.